INFLUENCE OF STEROID HORMONES IN WOMEN WITH MILD CATAMENIAL EPILEPSY - Hussain, Zahir; Qureshi, Masood A.; Hasan, K. Zaki; Aziz, Hasan (Journal of Ayub Medical College Abbottabad, 2006)
Background: In view of considerable differences of opinion regarding the reproductive steroid hormonal pathogenesis in catamenial epilepsy, hormonal analysis of estrogen and progesterone in catamenial epileptics for a precise correlation is of significant importance. Methods: Clinical, neurological and physiological assessments, and radioimmunoassay of plasma estradiol-17b and progesterone a day prior to the onset of menstruation were carried out in noncatamenial and mild catamenial epileptics having multiple frequency tonic-clonic (primary and secondary generalized) seizures. Results: Highly significant rise (p > 0.0001) of estradiol-17b was obtained for catamenial epileptics compared to normal subjects as well as noncatamenial epileptics (p > 0.02). However, nonsignificant fluctuations of progesterone were found for both catamenial and noncatamenial epileptics against normal subjects as well as catamenial versus noncatamenial epileptics. Conclusions: The present report suggests that estradiol have a precise role in the mild premenstrual exacerbation of seizures. However, no significant change in progesterone levels might have been due to mild exacerbation of seizures in these patients. Furthermore, we suggest the importance of how we collect and categorize the data and which pathophysiologic process/ clinicobiological mechanism is involved in patients with catamenial epilepsy. Contradictory results in literature may be related to differential levels of excitation/inhibition equilibrium during various cycle phases. More precise studies including the determination of the blood levels of antiepileptic drugs, however, are required. Key Words: Estradiol, progesterone, mild catamenial epilepsy